About Some Boundary Value Problems for Fractional PDE and their Numerical Solution. Issue 1 (December 2013) - Jovanović, Boško; Delić, Aleksandra; Vulkov, Lubin
Abstract A transmission initial‐boundary‐value problem in disjoint intervals for fractional in time diffusion equation is studied. Its well posedness in the corresponding Sobolev‐like spaces is proved. (© 2013 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)